(untitled) (UNED Research Journal, 2017)
The spectacled caiman, Caiman crocodilus, is ecologically and economicaly important in some areas of Latin America. In Costa Rica it is not abundant and there is a need for population data. I studied it in Caño Negro National Wildlife Refuge, Costa Rica, through the collection and comparison of previous studies and the incorporation of recent information. I made night boat trips with a 2 million lumen lamp (400m spectrum) and manually captured individuals under 60cm long. For larger sizes or animals located in areas of difficult access, I used Thompson ties and 2m long poles with an inserted rope, and captured 180 caiman. Most were sub-adults and there were 1:12 females per male, unusually high for the species and possibly caused by environmental conditions. The efects of global warming could disrupt the sex ratio and reproductive structure of spectacled caimans.